Tahap pengetahuan pelajar tentang konsep menutup aurat: suatu tinjauan umum - Suhid, Asmawati; Mohd Zain, Mohd Faizal; Ahmad, Abdul Muhsin; Che Noh, Mohd Aderi (Faculty of Education, University of Malaya, 2013)
The philosophy and concept of covering the aurah in Islam should be clearly understood by Muslims. This is because the standard of covering the aurah in Islam is very different from the views of other beliefs and philosophies. The obligation to cover the aurah as commanded by Allah SWT is very clear and detailed as well as universal in nature. When this concept is clearly understood, then there should be no confusion among Muslims to internalize and practice this ruling that is demanded by Islam. Related to this, a brief study was conducted involving students at one of the institutions of higher learning to get an idea about their perception and level of knowledge and understanding regarding the concept of covering the aurah. A total of 120 students participated in this study. The findings show that the level of students? knowledge pertaining to the obligation related to the covering of aurah is high (mean = 3.91). Besides discussing the findings, the researchers also proposed suggestions to further strengthen the efforts to induce awareness in students regarding the obligation of covering the aurah.